COVID-19 Racism, Internalized Racism, and Psychological Outcomes Among East Asians/East Asian Americans. (April 2022) - Ahn, Lydia HaRim; Yang, NaYeon; An, Mira
The present study investigated the psychological effects of racism on East Asians and East Asian Americans (EAEAAs) living in the United States during the COVID-19 pandemic using a mixed-methods approach. First, using an autoregressive cross-lagged panel analysis, we investigated the relations between COVID-19 racism, internalized racism, psychological distress, and social isolation among EAEAAs. We then examined the impact of the COVID-19 pandemic on EAEAAs using consensual qualitative research-modified. Quantitative findings showed that COVID-19 racism at Time 1 was associated with greater subsequent psychological distress, and COVID-19 racism at Time 2 was associated with greater levels of subsequent psychological distress and social isolation at Time 3, suggesting that COVID-19 racism predicted psychological distress and social isolation over time. Qualitative findings highlighted the prevalence of racism towards EAEAAs and the associated negative consequences. Findings demonstrate that EAEAAs living in the United States are at great risk due to the detrimental effects of racism during COVID-19.